Knowledge, attitudes, motivations and expectations regarding antimicrobial use among community members seeking care at the primary healthcare level: a scoping review protocol - Stephen M Campbell; Brian Godman; Eunice Bolanle Turawa; Nishana Ramdas; Johanna C Meyer; Natalie Schellack (BMJ Open, 2025)
Introduction Inappropriate antibiotic use in (primary healthcare, PHC) settings fuels antimicrobial resistance (AMR), threatens patient safety and burdens healthcare systems. Patients’ knowledge, attitudes, motivations and expectations play a crucial role in antibiotic use behaviour, especially in low-income and middle-income countries including South Africa. There is a need to ensure measures of antibiotic use, interventions and future guidance reflect cultural, community and demographic issues associated with patient views to reduce inappropriate use of antibiotics and associated AMR. The objective of this scoping review is to identify key themes surrounding knowledge, attitudes, motivations and expectations among patients and community members regarding antimicrobial use in PHC settings especially in low-income and middle-income countries.Methods and analysis This scoping review employs a comprehensive search strategy across multiple electronic databases, including OVID, Medline, PubMed and CINHAL, to identify studies addressing patients or community members seeking care at PHC facilities and exploring key drivers of antimicrobial use. The Covidence web-based platform will be used for literature screening and data extraction and the Critical Appraisal Skills Programme qualitative checklist will assess the quality of qualitative papers. Anticipated results will provide an overview of the current evidence base, enabling identification of knowledge gaps. A narrative synthesis of findings will summarise key themes and patterns in patients’ knowledge, attitudes, motivations and expectations related to antibiotic use across studies while considering methodological diversity and limitations.Ethics and dissemination Ethics approval is not required for this scoping review. The findings of this scoping review will be disseminated through publication in a peer-reviewed journal, presentation at relevant conferences and workshops, and collaboration with policy-makers and healthcare stakeholders.